Analisis Kepuasan Pelayanan Sekretariat DPRD Kota Sukabumi Terhadap Anggota DPRD Kota Sukabumi - Fatwa Adib Soetedjo; Dudih Gustian (LPPM STIKOM Tunas Bangsa, 2024)
To assess or evaluate the quality of performance services, the ability to analyze data using significant methods is required. The DPRD is a Regional People's Representative Institution which functions as an organizing element of Regional Government. In a government agency, service quality is a benchmark for an agency to assess employee quality, performance efficiency and effectiveness of coordination flows between one section and another. The Service Quality method is the right choice for analyzing the quality of performance in an agency. The subjects of this research were 22 of the 5 members of the Sukabumi City DPRD. The research results show positive results with a gap of 0.08 for performance measurement, reliability, empathy, responsiveness and assurance.